RESPONS SINTILASI SINYAL GPS SAAT BADAI GEOMAGNET DI LINTANG RENDAH - - Aswati (Lembaga Penerbangan dan Antariksa Nasional, 2006)
S4 in dex data of ISM (Ionospheric Scintillation Monitoring) at Pontianak and Pare-pare have been used to analyze the response of ionospheric scintillation during magnetic strom at low latitude. The ionospheric scintillation observed by a GPS receiver of L1 (1.57542 GHz) signals to measure both amplitude and phase variations during the geomagnetic storm of April 6, 2000 and July 15, 2000. Observation of S4 index during geomagnetic storm of April 7, 2000 at Pontianak and July 16, 2000 at Parepare did not show the main phase. This result is in agreement wiyh the hypothesis of the effect of the ring current in the generating or inhibition of F layer irregularities during magnetic storm. Since the minimum excursion of Dst during the magnetic storm on April 6 and July 15, 2000 are near midnight (24.00 UT) or around 07.00 Local Time (LT) on April 7 and July 16, 2000, so that the excursion categorized by excursion Dst takes place during daytime and well before sunset, where shown scintillation are inhibited.